China’s effect on Latin America’s international trade - Montenegro, Claudio E.; Pereira, Mariana; Soloaga, Isidro (Estudios de Economía, 2016)
Using a gravity model, this article presents an analysis of aggregate trade flows aimed at identifying China's impact on Latin America's trade. The results obtained indicate that: i) China's growth in the last years implied a growing supply of exports to this market from most countries in the World, including that of Latin American countries; ii) at the aggregate level, there was no indication that Chinese exports to third markets were crowding out LAC exports to those countries; and iii) a positive relationship between imports from China and exports to third markets was only found for the Southern Cone countries.